Light-ion production in the interaction of 175 MeV neutrons with iron and bismuth - Bevilacqua R. (2017)
We have measured double-differential (angle and energy) cross sections for light-ion (p, d, t, 3 He, and α) production in the interaction of quasi-monoenergetic 175 MeV neutrons with iron and bismuth. Measurements have been performed at the The Svedberg Laboratory, Uppsala (Sweden), using the Medley setup which allows low-energy thresholds and wide energy and angular ranges. Medley is a spectrometer system consisting of eight three-element telescopes placed at angles from 20° to 160°, in steps of 20°. Each telescope is composed of two silicon surface barrier detectors and a CsI(Tl) scintillator, to perform particle identification, fully stop the produced light-ions and measure their kinetic energy. The time-of-flight was used to reduce the contribution from the low energy tail in the accepted incident neutron spectrum. We report double-differential production cross sections for protons, deuterons, tritons, 3 He and α particles and compare them with model calculations with Talys-1.2.